Skin graft take rate among minor burns – A cohort study to investigate the effect of factors such as burn depth, burn size, and timing of the operation - Sinan Dogan; Arina Mahmoud; Ingrid Steinvall; Elin Albertsson; Elina Bergman; Jamila Halimi; Moustafa Elmasry (Burns Open, 2025)
Background: It has been known for decades that early excision of burns reduces morbidity and mortality. Early surgical excision and skin grafting has become the most important part of successful healing in burn management, especially in major burns. However, it is not entirely clear whether early excision and skin transplantation has the same advantages in smaller burns and there is no consensus on the timing of skin grafting in this group. The aim was to investigate the effect of timing and other factors for skin graft take rate among minor burns. Methods: This retrospective study included patients with thermal injury, a burn size smaller than 11 % total body surface area (TBSA), and who were treated with a skin graft operation. Take rate at the second dressing change after operation was used as main outcome, a cut-off of 95% take rate was for the multivariable logistic regression. Results: A total of 195 patients were included, median (IQR) age was 42 (9–68) years, 65 % were male, and median (IQR) area of deep burns was 2 (1–4) % of the body surface area (BSA). Multivariable regression showed that smaller area of deep burns and scalds (compared with flame and contact burns) were associated with a take rate of ≥ 95 %. Age, timing of the skin graft transplantation, and plasma C-reactive protein showed no independent effect on take rate. The regression model was significant but weak (ROC AUC 0.71, 95 % CI 0.62–0.79). Conclusion: Our results suggest that the extent and depth of the burn are the most important factors for skin graft take rate among minor burns, while timing of the transplantation is not associated with take rate for the skin graft. The advantageous effect of scalds may be interpreted to mean that scalds in general are more superficial than flame and contact burns, a difference that may not be detected by the use of a Lund and Browder chart. The conclusion is, however, tempered by the retrospective study design and the relatively low discriminatory power in our study.